Level of Efficiency of School Library in Bestlink College of the Philippines as Perceived by Grade 12 Humanities and Social Sciences Students: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
A library is a structure or area where various books are gathered and stored for reading.Books are the most important component of education because they increase our knowledge.Students today are facing an overwhelming number of sources to get the information theyneed, but findings or gathering information has become more complex, especially for thosewho are not familiar with libraries. The library fills the knowledge gap between what studentswant to know and what they are taught. The researchers developed this study to determinethe efficiency of the school library for Grade 12 Humanities and Social Sciences students atBestlink College of the Philippines.Based on the results, the level of efficiency of the school library as perceived by grade 12Humanities and Social Sciences students is described in terms of services, accessibility, andavailability as highly efficient. Additionally, there are some academic benefits the students canacquire in the school library in terms of technology and environment. Moreover, therespondents provide suggestions on how to determine the efficiency of school libraries invarious aspects.The discussion shows the summary of findings about the level of efficiency of a school libraryin Bestlink College of the Philippines as perceived by grade 12 Humanities and SocialSciences students, the academic benefits the students acquire in the school library, and therecommendations stated by the respondents. It includes the conclusions andrecommendations given by the researchers about the further spread of the use of schoollibraries.
Keywords: Education